China’s special economic zones: an analysis of policy to reduce regional disparities - Bret Crane; Chad Albrecht; Kristopher McKay Duffin; Conan Albrecht (Regional Studies, Regional Science, 2018)
There is no doubt that major regional disparities exist within China. The gap between its eastern coastal regions compared with the central and western regions has only grown wider over time. China’s special economic zones (SEZs) are defined as small geographical areas that allow the integration of free-market principles to attract additional foreign investment. However, the creation and success of SEZs has led to prosperity in the coastal regions of China, creating additional economic disparity between regions. This paper posits that one solution to reduce regional disparities is to extend the influence of the SEZs, or even set up new ones in different areas of the country, to spur investment and close the economic gaps.